Dynamic modeling of municipal solid waste incineration. (15th October 2020) - Magnanelli, Elisa; Tranås, Olaf Lehn; Carlsson, Per; Mosby, Jostein; Becidan, Michael
Abstract: In this work, a comprehensive dynamic model of a moving grate Waste-to-Energy plant is developed using MATLAB Simulink. The objective is to develop a reliable and flexible model which can reproduce the dynamic behavior of combustion chamber and boiler. For this purpose, an extensive number of process data is used both in model development and for validation. Contrary to previous works in literature, fluctuations in both waste properties and operational set points are taken into account. The validated model is then used to study the dynamic response of the plant to changes in important process parameters. As expected, the dynamic response of the plant is faster for changes in primary and secondary air than for changes in grate speed and waste flow. The steam production response is from 1 to 4 min slower than the flue gas oxygen concentration response. Moreover, the response time depends to a large extent on the properties of the waste; as an example, an increase in waste humidity from 25% to 35% results in a 21 min increase in the steam production response time. Such characterization of the dynamic response of the plant is fundamental to develop improved control strategies. Graphical abstract: Image 1 Highlights: A dynamic model of a moving grate Waste-to-Energy plant has been developed. The effect of waste composition on the dynamic plant response is analysed. Plant response was slower for higher moisture and ash content in the waste.